Laws as Tactics - Spade, Dean (Columbia Journal of Gender and Law, 2011)
This symposium invites us to consider the impact of Judith Butler’s work on legal scholarship in the area of gender and sexuality. I am interested in reflecting particularly on trans politics and law for two reasons. First, because Butler’s work has had such a significant impact on the emergence of the current iteration of trans politics of the 1990s and 2000s. Second, because I believe there is a great deal more that Butler’s work can offer to significant questions facing trans resistance formations as the field of trans legal rights advocacy institutionalizes and as trans legal scholarship engages and responds to that institutionalization. In particular, I am interested in how Butler’s work has provided analytical models for considering the role that norms and normalization play in both disciplinary and biopolitical modes of governance relating to gender. This analysis is essential to understanding the limitations of certain legal rights frameworks for addressing harms created by racialized and gendered systems of meaning and control.